Pengaruh Pendapatan Dan Gaya Hidup Terhadap Pola Konsumsi Masyarakat Muslim Di Surabaya Selama Masa Pandemi Covid-19 Ditinjau Dari Perspektif Etika Konsumsi Islam - Evi Maryadiningsih (CV ODIS, 2021)
The Covid-19 pandemic has had a considerable impact on various sectors of people's lives, including socio-economic interactions. This has resulted in many changes in people's consumption patterns to meet the needs of daily life. Islam emphasizes two things in meeting needs, prioritizing consumption that is more necessary and more useful and avoiding excessive consumption. The pattern of Muslim consumers prioritizes needs, not wants. Income affects the number of goods consumed. it is often found that with an increase in income, the goods consumed not only increase but also the quality of the goods becomes a concern. In addition to income, lifestyle is also a major factor in a person's consumerism. For someone who likes a luxurious lifestyle, the level of consumption is high. The purpose of this study was to determine the effect of income and lifestyle on consumption patterns. This research is quantitative research with a causal explanatory research design. With a population of Muslims in Surabaya and the sample is the congregation of Friday at the big mosques of each sub-district with a sample size of 100 respondents obtained by random sampling technique. The data collection technique used a questionnaire, the results of which were analyzed by multiple linear regression. The results of this study show that income and lifestyle affect the consumption patterns of the Muslim community in Surabaya during the COVID-19 pandemic.